Peroxisome Deficiency Impairs BDNF Signaling and Memory - Abe, Yuichi; Nishimura, Yoshiki; Nakamura, Kaori; Tamura, Shigehiko; Honsho, Masanori; Udo, Hiroshi; Yamashita, Toshihide; Fujiki, Yukio (Frontiers in Cell and Developmental Biology, 2020)
Peroxisome is an intracellular organelle that functions in essential metabolic pathways including β-oxidation of very-long-chain fatty acids and biosynthesis of plasmalogens. Peroxisome biogenesis disorders (PBDs) manifest severe dysfunction in multiple organs including central nervous system (CNS), whilst the pathogenic mechanisms are largely unknown. We recently reported that peroxisome-deficient neural cells secrete an increased level of brain-derived neurotrophic factor (BDNF), resulting in the cerebellar malformation. Peroxisomal functions in adulthood brain have been little investigated. To induce the peroxisome deficiency in adulthood brain, we here established tamoxifen-inducible conditional Pex2-knockout mouse. Peroxisome deficiency in the conditional Pex2-knockout adult mouse brain induces the upregulated expression of BDNF and its inactive receptor TrkB-T1 in hippocampus, which notably results in memory disturbance. Our results suggest that peroxisome deficiency gives rise to the dysfunction of hippocampal circuit via the impaired BDNF signaling.